Organizational culture and leaderhsip - "Schein, Edgar H." (San Francisco, 1991)
Presents a comprehensive analysis of organizational culture - what it is, how it develops, and how it functions in relation to managerial style and organizational effectiveness.
Keywords: Corporate culture